THE PERCEPTION OF ORGANIC FISHERY PRODUCTS IN SOUTH –EAST DEVELOPMENT REGION OF ROMANIA - Zugravu Gheorghe, Adrian; Turek Rahoveanu, Maria Magdalena; Turek Rahoveanu, Adrian (Economics of Agriculture, 2012)
The paper follows two main objectives: to understand consumers perception and image of fishery ecological products and to identify communication levers in order to improve the perceived image of fishery products. Orientations in terms of communication are product-focused and aim at enhancing the reputation of products, consequently with impact on product consumption. The present research is focused on the Fishery products, regardless of their presentation – fresh, frozen or processed. This paper conducted a questionnaire survey of Romanian consumers perception toward fishery products. The empirical study with tractor brands indicated that farmers shown different awareness to domestic and foreign fish ecologic products. National fishery ecological products got more attention from the consumers. Foreign fishery ecological products had higher perceptive price, but Romanian fishery ecological products acquired higher perceptive value, and got a better rank in the preference list and in the purchase intention of the consumers.